QRIS ADOPTION IN RELIGIOUS ORGANIZATIONS: EXTENDED UTAUT2 WITH GEOGRAPHIC MODERATION - Munthe, Mei Hotma Mariati; Sijabat, Jadongan; Siahaan, Johan Putra Octavian (LPPM Universitas Jambi, 2026)
This study examines the determinants of Quick Response Code Indonesian Standard (QRIS) mobile payment usage within religious organizations by applying an extended Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework. The model integrates perceived risk, perceived security, and exposure to innovation, while testing geographic location as a moderating variable. Using a quantitative approach, a survey was conducted among 4,516 congregants of the Huria Kristen Batak Protestan (HKBP) Church across 32 districts in Indonesia, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that performance expectancy, facilitating conditions, habit, perceived security, and exposure to innovation significantly influence QRIS usage, with habit emerging as the most dominant predictor. In contrast, effort expectancy and perceived risk do not show significant effects, suggesting that ease of use has become standardized and institutional trust mitigates perceived risk in this context. Geographic location significantly moderates the effects of effort expectancy, facilitating conditions, and habit, highlighting the role of regional digital infrastructure disparities. The model explains 74.7% of the variance in QRIS usage. This study contributes to the literature by extending UTAUT2 into a trust-based non-profit institutional context and introducing geographic moderation in digital payment adoption research, while providing practical insights for policymakers and religious institutions to design more inclusive and infrastructure-sensitive digital financial strategies.